A Pilot COVID-19 Surveillance Program at the Zendrini Center in Milan (Italy) for Unaccompanied Foreign Minors - Stefano Tambuzzi; Marco Cummaudo; Lidia Maggioni; Stefania Tritella; Barbara Lucchesi; Paola Montedoro; Immacolata Agostinelli; Sofia Trezzi; Antonella Maria Costantino; Rossana Mazzoni; Michela Marognoli; Pasquale Poppa; et al. (MDPI AG, 2022)
During the COVID-19 pandemic, not only crowded refugee camps and immigration detention centers, but also receptions were places in which outbreaks occurred. To date there has been no report of the application of a COVID-19 surveillance system in reception centers for unaccompanied foreign minors only, who most of all deserve the utmost attention. Aware of this critical issue, we implemented a pilot COVID-19 surveillance program at the Zendrini center in Milan. It was started in September 2021 and was carried out for 4 months. Nasopharyngeal antigenic swabs were adopted. One day a week, two forensic physicians performed the first antigenic swab to minors who had just entered the center, or a monitoring swab after 15 days to those who were still hosted at the center. Operators were also swabbed for surveillance. A total of 80 subjects were enrolled and divided into 68 (72.5%) unaccompanied foreign minors and 22 (27.5%) operators. A total of 178 antigenic nasopharyngeal swabs were performed and tested negative. Regarding the monitoring activities, it was found that the minimum number of swabs per subject was 1 and the maximum number was 7, with an average value of 2.2 per individual. Having been able to confirm the absence of SARS-CoV-2 within the community represented a way to protect individual and collective health that could not have been pursued otherwise. Only inclusive approaches can allow communities and societies to respond more effectively to this crisis, and reduce the risk of future ones, intended as both upcoming COVID-19 waves and new infectious diseases.